Tumor Immune Microenvironment and Its Related miRNAs in Tumor Progression - Xing, Yingying; Ruan, Guojing; Ni, Haiwei; Qin, Hai; Chen, Simiao; Gu, Xinyue; Shang, Jiamin; Zhou, Yantong; Tao, Xi; Zheng, Lufeng (Frontiers in Immunology, 2021)
MiRNA is a type of small non-coding RNA, by regulating downstream gene expression that affects the progression of multiple diseases, especially cancer. Immune cells in the area around a tumor constitute the tumor immune microenvironment. These cells include lymphocytes with tumor suppressor effects such as CD8+ T cells and natural killer cells, as well as some tumor-promoting cells with immunosuppressive functions, such as regulatory T cells and myeloid-derived suppressor cells. MiRNA can affect the tumor immune microenvironment by regulating the function of immune cells, which in turn modulates the progression of tumor cells. Investigating the role of miRNA in regulating the tumor immune microenvironment will help elucidate the specific mechanisms of interaction between immune cells and tumor cells, and may facilitate the use of miRNA as a predictor of immune disorders in tumor progression. This review summarizes the multifarious roles of miRNA in tumor progression through regulation of the tumor immune microenvironment, and provides guidance for the development of miRNA drugs to treat tumors and for the use of miRNA as an auxiliary means in tumor immunotherapy.